Children’s literature in the classroom: Beginning Literacy and fundamental pillars - Oddsdóttir, Rannveig; Haraldsdóttir, Halldóra; Gunnbjörnsdóttir, Jenný (Menntavísindasvið Háskóla Íslands, 2018)
The educational policy that appears in the Icelandic National Curriculum Guide for preschools, compulsory schools and upper secondary schools is based on six fundamental pillars of education. These fundamental pillars are: literacy, sustainability, health and welfare, democracy and human rights, equality and creativity. The fundamental pillars refer to social, cultural, environmental and ecological literacy so that children and youth may develop mentally and physically, thrive in society and cooperate with others. The fundamental pillars also refer to a vision of the future, ability and will to influence and be active in maintaining, changing and developing society. The fundamental pillars are an intrinsic part of school activities; the concepts that they are based on are to be reflected in the working methods, communication and atmosphere of schools.In this article, we discuss how teachers can use children’s literature to promote the fundamental pillars in grade 1 and 2 in schools using the teaching method Beginning Literacy. Beginning Literacy is a development project on literacy education in the first two years of primary schools in Iceland. Beginning Literacy is built on an interactive model where the emphasis is on balancing the various aspects of literacy and decoding skills and the construction of meaning according to students’ background knowledge. In Beginning Literacy, this balance is maintained by structuring the teaching through three sequential phases. In the first phase, children are exposed to an authentic text (usually a children’s book). The text is read aloud to them by their teachers and discussed for comprehension. Then the children investigate the texts to address the technical aspects of reading and finally create their own texts. Children’s literature can be informative about different aspects of life and society. It can work as a window to other people’s lives and circumstances or a mirror of your own life, feelings and thoughts. Thus, children’s literature can help children understand ...